2016
DOI: 10.1073/pnas.1605063113
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic β 2 -adrenergic receptors mediate hippocampal long-term memory consolidation

Abstract: Emotionally relevant experiences form strong and long-lasting memories by critically engaging the stress hormone/neurotransmitter noradrenaline, which mediates and modulates the consolidation of these memories. Noradrenaline acts through adrenergic receptors (ARs), of which β 2 -adrenergic receptors (βARs) are of particular importance. The differential anatomical and cellular distribution of βAR subtypes in the brain suggests that they play distinct roles in memory processing, although much about their specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
173
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(185 citation statements)
references
References 50 publications
11
173
0
1
Order By: Relevance
“…The molecular mechanisms of both the acute and adaptive regulation of memory by glucocorticoids have been elucidated (2,10), and studies have shown that emotional stress enhances learning in an acute manner (7). In parallel to our study, other studies have revealed that hippocampal long-term consolidation of fear-based contextual memory can be mediated by β2AR in astrocytes (24). In the present study, we used the Morris water maze and OR experiments as models to enable the activation of specific βAR signaling using pharmaceutical intervention, at the exclusion of the excessive activation of other endogenous stress signaling pathways.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The molecular mechanisms of both the acute and adaptive regulation of memory by glucocorticoids have been elucidated (2,10), and studies have shown that emotional stress enhances learning in an acute manner (7). In parallel to our study, other studies have revealed that hippocampal long-term consolidation of fear-based contextual memory can be mediated by β2AR in astrocytes (24). In the present study, we used the Morris water maze and OR experiments as models to enable the activation of specific βAR signaling using pharmaceutical intervention, at the exclusion of the excessive activation of other endogenous stress signaling pathways.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to its neuronal function, β2AR is essential for stress-induced memory consolidation through glycogen breakdown (1923). Although these studies demonstrated the role of acute β2AR activation in astrocyte glucose metabolism and synaptic activity in a disease model, the adaptive effects of β2AR activation in learning and memory have just begun to be systematically studied (24), and the signaling subnetwork underlying β2AR activity remains elusive. Therefore, we examined the effects of the β2AR agonist formoterol on mouse learning and memory abilities using the Morris water maze and an object recognition (OR) task over various time periods.…”
mentioning
confidence: 99%
“…Previous studies indicated the particularity and interconnected functionality of hippocampal neurons and astrocytes, suggesting the possibility of region-specific alterations involving the two cell types. Both neurons and astrocytes, as well as their interactions, were implicated in learning and memory processes localized in the hippocampus (Henneberger et al 2010;Suzuki et al 2011;Ota et al 2013;Hassanpoor et al 2014;Tadi et al 2015;Gao et al 2016;Pabst et al 2016). Astrocytes were further shown to contribute to the integration of adult-born neurons in the hippocampus, although adult hippocampal neurogenesis in humans remains controversial (Krzisch et al 2015;Sultan et al 2015;Sorrells et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen turnover, i.e., interspersed glycogen synthesis and glycogenolysis, is indispensable during learning Hertz et al 2013). The acute memory-enhancing, glycogenolysis-dependent effect of both fluoxetine and paroxetine has been mentioned (O'Dowd et al 1994;1995;Gibbs and Hertz 2014;Suzuki et al 2011;Gibbs and Hertz 2014;Gao et al 2016). Knock-out of brain glycogen synthase abolishes learning of new motor and cognitive skills (Duran et al 2013).…”
Section: Page 10 Of 27 Psychopharmacologymentioning
confidence: 99%